Is Social Media Engagement and Sentiments the Right Metric for Investing in Crypto-Currencies? Implications for Entrepreneurs and Investors - Sakunia, Debashish; Parida, Biswajita (Indian Journal of Research in Capital Markets, 2023)
Purpose : This study examined the relationship between social media engagement and cryptocurrency prices, considering information asymmetry and lack of historic data in the cryptocurrency market. Approach : The study analyzed the correlation between social media engagement and prices of major cryptocurrencies using a graphical approach. Data on daily social media reach, mentions, engagements, and cryptocurrency price changes were collected for three sets of 16 days each. Findings : The study showed diverse relationships between social media engagement and cryptocurrency prices. Bitcoin exhibited a strong positive correlation, Altcoins showed a moderately positive correlation, and Stable Coins demonstrated a weak negative correlation. No significant correlation was observed for utility tokens and security tokens. Practical Implications : The study suggested that entrepreneurs should focus on creating engaging content to boost cryptocurrency prices instead of relying solely on social media engagement. Retail investors should exercise caution when using social media for investment decisions, as it may not accurately reflect a cryptocurrency’s true value or potential. Originality/Value : This study contributed to the understanding of the complex relationship between social media engagement and cryptocurrency prices. The study highlighted the need for thorough research and consideration of multiple factors when making investment decisions in the cryptocurrency market. Conclusion and Implications : The study’s implications extend to entrepreneurs and retail investors in the cryptocurrency market. Entrepreneurs should consider social media engagement as one factor among many to increase cryptocurrency prices and be aware of its limitations. Retail investors should conduct thorough research and consider multiple factors, as relying solely on social media engagement may not accurately assess a cryptocurrency’s potential.